An Overview of Exploitation and Utilization of Shallow Geothermal Energy in Northwest China - Sun, Chang; Ju, Xiaolei (Transactions on Environment, Energy and Earth Sciences, 2024)
Geothermal energy, as a non-carbon-based energy, serves as a crucial way to achieve the goal for “carbon reductions in two stages”, namely the target of peaking carbon dioxide emissions by 2030 and achieving carbon neutrality by 2060. China is a large country with abundant mesothermal-epithermal geothermal resources. Its national potential geothermal resources account for nearly 8% of those in the world, and geothermal resources have been developed and utilized for nearly 50 years in China. According to incomplete statistics, the geothermal fields in Northwest China accounts for 10% of those in the country, and the stored thermal energy in Northwest China accounts for 3.34% of the total in the country. In order to probe into the potential of geothermal resources in Northwest China and their value in the goal for “carbon reductions in two stages”, this paper summarizes the shallow geothermal energy resource endowment in Northwest China, briefly introduces the status quo of shallow geothermal energy exploitation and utilization and existing problems.